2023
DOI: 10.1186/s13018-023-04003-0
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of long noncoding RNA HULC inhibits the inflammatory response in ankylosing spondylitis by reducing miR-556-5p-mediated YAP1 expression

LuLu Yi,
ChangJun Song,
YuanYuan Liu
et al.

Abstract: Objective Ankylosing spondylitis (AS) is a progressive systemic disease characterized by a chronic inflammatory response in the sacroiliac joints and spine. Long noncoding RNAs suggest significant actions in the progression of AS. Therefore, a specific lncRNA, highly upregulated in liver cancer (HULC), was studied here regarding its functions and related mechanisms in AS. Methods Measurements of miR-556-5p, HULC, and YAP1 expression were performed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…As previously discussed, HULC has been identified as a potential influencer in the development of AS by regulating the expression of miR-556-5p and YAP1 ( Yi et al, 2023 ). Additionally, elevated levels of HULC and YAP1, coupled with reduced miR-556-5p expression, were observed in the spinal cartilage of AS mice, indicating that HULC contributes to the pathological injury of spinal cartilage.…”
Section: Lncrnas Involved In the Pathogenesis Of Asmentioning
confidence: 94%
See 1 more Smart Citation
“…As previously discussed, HULC has been identified as a potential influencer in the development of AS by regulating the expression of miR-556-5p and YAP1 ( Yi et al, 2023 ). Additionally, elevated levels of HULC and YAP1, coupled with reduced miR-556-5p expression, were observed in the spinal cartilage of AS mice, indicating that HULC contributes to the pathological injury of spinal cartilage.…”
Section: Lncrnas Involved In the Pathogenesis Of Asmentioning
confidence: 94%
“…A specific lncRNA, highly upregulated in liver cancer (HULC), has been investigated for its functions and related mechanisms in AS ( Yi et al, 2023 ). Their research demonstrated that the silencing of HULC promotes chondrocyte proliferation while reducing apoptosis and inflammation in AS.…”
Section: Lncrnas Involved In the Pathogenesis Of Asmentioning
confidence: 99%